Learning a new balance task: The influence of prior motor practice on training adaptations. Issue 5 (4th May 2023) - Keller, Martin; Roth, Ralf; Achermann, Samuel; Faude, Oliver
ABSTRACT: Prior motor experience is thought to aid in the acquisition of new skills. However, studies have shown that balance training does not promote learning of a subsequent balance task. These results stand in contrast to the learning-to-learn paradigm, which is well described for other tasks. We therefore tested if a coordinative affinity between tasks is needed to achieve a learning-to-learn for balance control. Three groups trained different motor tasks during training phase1 (coordination ladder (COOR); bipedal wobble board (2WB); single-leg wobble board (1WB)). During training phase2, all groups trained a tiltboard balance task. Task-specific and transfer effects were evaluated for phase1. A potential learning-to-learn effect was evaluated by comparing the acquisition rates from phase2 for the tiltboard task that was used for training and testing. The results indicate task-specific adaptations after phase1 for 1WB. In contrast, 2WB showed similar improvements than 1WB and COOR (effect sizes: −0.31 to −0.38) when tested on the wobble board with bipedal stance indicating no task-specific improvement for 2WB. For phase2, the linear regression analysis showed larger adaptations for 1WB and 2WB when compared to COOR. This effect implies some uncertainty due to overlapping confidence intervals. Task-specific adaptations after phase1 were found for 1WB but not 2WB. It is discussed that the difficulty of the training task could explain these contrasting results. During phase2, larger adaptations were found for both groups that trained balance tasks during phase1. Thus, despite some uncertainty, prior balance training appears to promote adaptations of a subsequently learned balance task. Highlights Prior balance training augments the learning of a new balance task if the two tasks share certain coordinative features. The concept of "learning to learn" can probably be applied to postural control, although further studies are needed. Balance training results (partly) in task-specific adaptations with no immediate transfer to other (but unrelated) balance tasks.